Standardization of Basic Movement “Belanjakan” of Martial Arts on East Lombok Regency - Hidayatullah, Muhammad Riyan; Rahayu, Tandiyo; Wahyudi, Agung (Journal of Physical Education and Sports, 2019)
Standardization of basic movements of “Belanjakan” martial is intended to explore, develop, and preserve martial arts that grow and develop as a culture of Masbagik people of East Lombok Regency. The purpose of the study is to examine and analyze the basic movements of stance, footstep patterns, defense, and attacks "Belanjakan" martial arts. Qualitative research uses research design case studies. The object of research is “Belanjakan” martial arts. The subject of the research was Pepadu "Belanjakan" in Masbagik District. Data collection techniques and instruments use observation, interview, documentation, and triangulation techniques. Data analysis is carried out based on an interactive analysis model (flow model). The research results of the standard basic movements "Belanjakan" martial arts include the basic stance of "Belanjakan" using respect, fighting stance of “Belanjakan” martial using (upper fighting stance and lower fighting stance) and the front horses. The footstep pattern in "Belanjakan" in terms of how it is implemented includes lifting and sliding, while in terms of its movement patterns include: straight and zig-zag pattern. The basic movement of "Belanjakan" defense uses catch accompanied by slamming and locking. The basic movement of the "Belanjakan" attack uses the legs or feet with kick techniques. The conclusions of the research compiled the standardization of the basic movements of the "Belanjakan" martial arts that were practical, efficient and interesting. It is expected that the "Belanjakan" martial arts will become the regional collective pride and tourist attraction. Suggestions for developing a more practical and efficient basic movement "Belanjakan" martial arts so that people are interested in learning martial arts as a characteristic of Masbagik indigenous culture.